Educational Technology of the Liberal Arts and Sciences Model Application in the Training of Lawyers - M. A. Dorofeeva (Теоретическая и прикладная юриспруденция)
This article describes the methods of teaching critical thinking to law students. Problems of the lack of functional literacy and weak critical thinking, which are crucial for successful professional activity in the conditions of the fourth industrial revolution, among junior students are presented. The authors propose to apply the methods of the Liberal Arts and Sciences within the disciplines of theory of state and law, history of state and law, philosophy of law, history of political and legal doctrines, history of legal science, etc. to correct functional illiteracy and form critical thinking.